Comparison of the effects of three different dehorning techniques on behavior and wound healing in feeder cattle in a western Kansas feedlot - Neely, Clement D. (Kansas State University, 2013)
Cross-bred horned steers and heifers (n = 40; BW = 311.8 ± 4.7 kgs.) were used to determine the effect of dehorning methods on pain, cattle behavior and wound healing. Cattle were blocked by weight and randomly assigned to 1 of 4 treatments: 1) control (CON); 2) banded using high tension elastic rubber (BAND); 3) mechanically removed (MECH); or 4) tipped (TIP). Vocalization and behavior were recorded during the dehorning process. Wound healing scores, attitude, gait and posture, appetite, and lying were recorded daily. Data were analyzed using the Wilcoxon Rank Sum Test of SAS (Cary, NC). Vocalization scores were highest for MECH, and the BAND cattle vocalized more than TIP and CON (P < 0.05). There were treatment effects for gait and posture (P = 0.03), appetite (P = 0.01) and lying scores (P < 0.01), BAND cattle had higher scores (P < 0.10) in these parameters compared to MECH, TIP and CON cattle. There was treatment by time interactions for attitude (P < 0.01), horn bud (P < 0.01) and bleeding (P < 0.01). BAND cattle had increased attitude scores in weeks 1, 3 and 4 (P < 0.10), increased hornbud scores in weeks 3 and 4 (P < 0.05) and increased bleeding scores in week 3 (P < 0.05). These data indicate that MECH is a painful procedure for cattle at the time of the procedure. Banding to remove horns from cattle is not recommended based on the data and observations from this study.
Keywords: Dehorning; Cattle; Pain; Animal welfare; Veterinary Medicine (0778)